2007
DOI: 10.1016/j.cub.2007.05.068
|View full text |Cite
|
Sign up to set email alerts
|

Social Cognition in Humans

Abstract: We review a diversity of studies of human social interaction and highlight the importance of social signals. We also discuss recent findings from social cognitive neuroscience that explore the brain basis of the capacity for processing social signals. These signals enable us to learn about the world from others, to learn about other people, and to create a shared social world. Social signals can be processed automatically by the receiver and may be unconsciously emitted by the sender. These signals are non-ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
393
3
11

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 564 publications
(436 citation statements)
references
References 102 publications
10
393
3
11
Order By: Relevance
“…T he amygdala is considered a critical node of the "social brain" that contributes to myriad social behaviors exhibited by primates (1)(2)(3)(4). Neurons in both the monkey (5) and human amygdala (6) respond prominently to faces, and lesions of the monkey amygdala result in complex impairments in social behavior (7,8).…”
mentioning
confidence: 99%
“…T he amygdala is considered a critical node of the "social brain" that contributes to myriad social behaviors exhibited by primates (1)(2)(3)(4). Neurons in both the monkey (5) and human amygdala (6) respond prominently to faces, and lesions of the monkey amygdala result in complex impairments in social behavior (7,8).…”
mentioning
confidence: 99%
“…Recent research has suggested that alongside impairments in understanding other's mental states (Baron-Cohen et al 1985;Frith and Frith 2007;Frith 2012;Senju 2012), people with ASD also have difficulty with taking another person's visual perspective (Hamilton et al 2009). Hamilton and colleagues found that whilst children with autism were impaired at visual perspective taking (VPT), they showed unimpaired performance on a task involving a non-social spatial transformation (mental rotation).…”
mentioning
confidence: 99%
“…We become capable of learning what motivates other people in their social interactions, even if these do not directly involve us. All these skills map onto schemas that are encoded in an associative network in memory and is orchestrated to ensure normal, skilled social adaptation (1).…”
mentioning
confidence: 99%